Where does scientific uncertainty come from, and from whom? Mapping perspectives of natural hazards science advice - Doyle EEH; Thompson J; Hill S; Williams M; Paton D; Harrison S; Bostrom A; Becker J (Elsevier, 2023)
The science associated with assessing natural hazard phenomena and the risks they pose contains many layers of complex and interacting elements, resulting in diverse sources of uncertainty. This creates a challenge for effective communication, which must consider how people perceive that uncertainty. Thus, we conducted twenty-five mental model interviews in Aotearoa New Zealand with participants ranging from scientists to policy writers and emergency managers, and through to the public. The interviews included three phases: an initial elicitation of free thoughts about uncertainty, a mental model mapping activity, and a semi-structured interview protocol to explore further questions about scientific processes and their personal philosophy of science. Qualitative analysis led to the construction of key themes, including: (a) understanding that, in addition to data sources, the ‘actors’ involved can also be sources of uncertainty; (b) acknowledging that factors such as governance and funding decisions partly determine uncertainty; (c) the influence of assumptions about expected human behaviours contributing to “known unknowns'; and (d) the difficulty of defining what uncertainty actually is. Participants additionally highlighted the positive role of uncertainty for promoting debate and as a catalyst for further inquiry. They also demonstrated a level of comfort with uncertainty and advocated for ‘sitting with uncertainty’ for transparent reporting in advice. Additional influences included: an individual's understanding of societal factors; the role of emotions; using outcomes as a scaffold for interpretation; and the complex and noisy communications landscape. Each of these require further investigation to enhance the communication of scientific uncertainty.
Keywords: Uncertainty; Mental models; Natural hazards; Societal and economic factor; Emotions; Communication